2023
DOI: 10.3390/life13101993
|View full text |Cite
|
Sign up to set email alerts
|

Co-Effects of Nitrogen Fertilizer and Straw-Decomposing Microbial Inoculant on Decomposition and Transformation of Field Composted Wheat Straw

Hiba Shaghaleh,
Yuanpeng Zhu,
Xinyi Shi
et al.

Abstract: Although straw is an abundant and useful agricultural byproduct, it, however, exhibits hardly any decomposition and transformation. Despite the successful application of chemical and biological substrates for accelerating straw decomposition, the co-effects and mechanisms involved are still unknown. Herein, we performed a 120 day field trial to examine the co-effects of a nitrogen fertilizer (N) and a straw-decomposing microbial inoculant (SDMI) on the straw mass, nutrient release, and the straw chemical struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Studies have shown that increasing microbial activity and population can accelerate stalk decomposition [5,6]. For instance, research by Hiba Shaghaleh et al [7] highlighted the addition of the N fertilizer and microorganisms accelerated the straw decomposition. Similarly, Zhang et al [8].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that increasing microbial activity and population can accelerate stalk decomposition [5,6]. For instance, research by Hiba Shaghaleh et al [7] highlighted the addition of the N fertilizer and microorganisms accelerated the straw decomposition. Similarly, Zhang et al [8].…”
Section: Introductionmentioning
confidence: 99%